MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN PROBLEM BASED LEARNING(PBL) BERBANTUAN MEDIA FLASH CARD KELAS III SDN 10 KOTO BARU - Angellya Novel Asmita (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2025)
The low science learning outcomes of third-grade students at SDN 10 Koto Baru highlight the importance of teachers using creativity in their teaching methods. Based on assessments of students' scientific understanding, it was found that students still demonstrated low performance in science subjects. The objective of this research project is to improve student learning outcomes through the implementation of the Problem-Based Learning (PBL) model. This study is classified as Classroom Action Research (CAR), with a methodology that includes the stages of planning, implementation, observation, and reflection. The research was carried out in two cycles.Tests were used as the data collection method in each cycle. Data analysis was conducted using both qualitative and quantitative descriptive approaches. With a mastery level of 92%, the findings indicate that teaching using the Problem-Based Learning model can effectively improve students' learning outcomes in science subjects.